2007
DOI: 10.1074/jbc.m704867200
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Stimulates Polynucleotide Kinase by Enhancing Its Damage Discrimination and Displacement from DNA Repair Intermediates

Abstract: Human polynucleotide kinase (hPNK) is required for processing and rejoining DNA strand break termini. The 5-DNA kinase and 3-phosphatase activities of hPNK can be stimulated by the "scaffold" protein XRCC1, but the mechanism remains to be fully elucidated. Using a variety of fluorescence techniques, we examined the interaction of hPNK with XRCC1 and substrates that model DNA single-strand breaks. hPNK binding to substrates with 5-OH termini was only ϳ5-fold tighter than that to identical DNA molecules with 5-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 41 publications
(64 reference statements)
6
56
0
Order By: Relevance
“…One possibility is that interaction with XRCC1 ensures that PNK activity is not rate limiting during SSBR in vivo. This idea is consistent with the observation that XRCC1 stimulates PNK activity in vitro at limiting concentrations of the latter enzyme, possibly by dissociating PNK from its DNA product and thereby increasing the enzyme turnover rate (32,54). However, interaction with XRCC1 also might promote the recruitment or accumulation of PNK at chromosomal SSBs, because the appearance of this protein in subnuclear foci is reduced in EM9-XH CKM cells following oxidative stress (30).…”
Section: Discussionsupporting
confidence: 77%
“…One possibility is that interaction with XRCC1 ensures that PNK activity is not rate limiting during SSBR in vivo. This idea is consistent with the observation that XRCC1 stimulates PNK activity in vitro at limiting concentrations of the latter enzyme, possibly by dissociating PNK from its DNA product and thereby increasing the enzyme turnover rate (32,54). However, interaction with XRCC1 also might promote the recruitment or accumulation of PNK at chromosomal SSBs, because the appearance of this protein in subnuclear foci is reduced in EM9-XH CKM cells following oxidative stress (30).…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with this model, PNKP has been shown to have significant affinity for the products of both its kinase and phosphatase domains (22). Interactions with the single-strand repair scaffold protein, XRCC1 or the NHEJ scaffold protein, XRCC4, facilitate PNKP product release, consistent with the idea that these scaffold proteins organize multistep, coordinated repair of DNA damage (23)(24)(25).…”
Section: Resultssupporting
confidence: 58%
“…Thus, it is likely that the FHA domain of PNKP recognizes phosphate groups in other molecule besides PAR, which is important for the stability of PNKP at DNA damage sites. It has been reported that PNKP interacted with XRCC1 (Whitehouse et al 2001;Mani et al 2007), which also recognizes PAR at DNA damage sites. However, the recruitment of PNKP to DNA damage sites is independent of XRCC1 (Supplemental Fig.…”
Section: Computational Analysis Of the Par-binding Pockets In The Fhamentioning
confidence: 99%